Investigating Palm Oil Mill Effluent Furnace Heating Pre-treatment for Biogas Production - Kamaruzaman N.; Mohamed H.; Suhaimi N.E.; Mohd Roslan M.E.; Shamsuddin A.H. (Springer Science and Business Media Deutschland GmbH, 2023)
Effluent treatment; Effluents; Furnaces; Heating; Methane; Oil shale; Palm oil; Wastewater treatment; Biochemical methane potential; Biogas production; Biomethane; Furnace heating; Heating method; Palm oil mill effluents; Pre-treatments; Pretreatment process; Production capabilities; Wastewater sludge; Biogas